subtitusi tepung terigu dengan tepung nipah terhadap karakteristik butter cake dan daya terima panelis - Surhaini; Mursyid, Muhammad; D, Gita (Department of Technology of Agricultural product (THP) Jambi University, 2018)
Purpose the research to determine the effect substitution ofwheat flour with nypa flour to butter cake characteristics and acceptance of organoleptics test and to obstain the best formulation of nypa flour. This research used random completely design with consist of six treatment. Each treatment perform three replication to obstain eighteen units of experiment. The treatment use wereN1T1nypa flour 0% and 100% wheat flour; N2T2nypa flour 20% and wheat flour80% N3T3nypa flour 40% and wheat flour 60% ;N4T4 nypa flour 60% and wheat flour 40%.N5T5, nypa flour 80% and wheat flour 20%, N6T6 nypa flour 100% and wheat flour 20%.. The result showed that used nypa flour significantly effect on water content, protein content, texture analyze, expand power, texture and the overall sensory was liked by panelist . The best treatment of substitution with wheat flour was N3T3 (wheat flour substitution with 40% flour nypa). The best butter cake with water content 12,17%, protein content 5,69%, texture 180,13 gF, expand power 31,44% and the best organoleptic with taste 5,00 (very like), and overall acceptance 4 (like).